Trait association and path analysis for yield of cassava genotypes grown in various agroecologies in Nigeria - Aina, O.; Dixon, A.; Akinrinde, E. (2004)
The association among different traits and their direct and indirect influence on yield using path analysis were conducted with 30 broad-based and diverse cassava genotypes evaluated at four agroecological zones in Nigeria. Traits evaluated include reactions of the genotypes to prevalent pest and diseases, and shoot and root characteristics. The result showed that cassava mosaic disease (CMD) incidence and severity were significantly but negatively correlated (P<0.01) with root yield, with correlation coefficients of -0.44 and -0.45, respectively. Root yield was significantly and positively correlated with number of stands harvested (r=0.81), harvest index (r= 0.74) and stay green ability (r= 0.37). Positive and significant correlation (P<0.01) between root yield and total root number (r= 0.91), number of large sized rrots (0.57), number of medium sized roots (r=0.95), and number of small sized roots (r= 0.77) were also obtained. However, the results of path analysis showed that the largest direct effect on root yield was obtained for total number of roots harvested (direct path coefficient = 0.64), and was followed by number of medium sized roots (direct path coefficient = 0.25), and number of large sized roots (direct path coefficient = 0.22). Negative direct effects on the root yield were obtained with number of small sized roots (direct path coefficient = -0.20) and stay green ability (direct path coefficient = -0.14). It is evident from this study that total number of roots, numberof medium and large sized roots were important contributing factors to yield enhancement in cassava and could be used as selection criteria in the genetic improvement of cassava.